2014
DOI: 10.1038/cmi.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 signaling pathways are required for recombinant Brucella abortus BCSP31-induced cytokine production, functional upregulation of mouse macrophages, and the Th1 immune response in vivo and in vitro

Abstract: Brucella abortus is a zoonotic Gram-negative pathogen that causes brucelosis in ruminants and humans. Toll-like receptors (TLRs) recognize Brucella abortus and initiate antigen-presenting cell activities that affect both innate and adaptive immunity. In this study, we focused on recombinant Brucella cell-surface protein 31 (rBCSP31) to determine its effects on mouse macrophages. Our results demonstrated that rBCSP31 induced TNF-a, IL-6 and IL-12p40 production, which depended on the activation of mitogen-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 91 publications
(94 reference statements)
6
40
0
Order By: Relevance
“…Although most lipoproteins signal via TLR2, but our data showed that rLsa21 signals via both TLR2 and TLR4. This finding is consistent with various previous reports demonstrating the production of proinflammatory cytokines and chemokines through TLR2/4 by Leptospira hemolysins23, whole Leptospira or their purified components (LPS, membrane proteins) but also proteins from other bacterial pathogens like Brucella and Mycobacterium 38394041. Our results showed that rLsa21 induced cytokine production mainly through MYD88 dependent signaling pathway as there was a reduced concentration of cytokines (IL-6 and TNF-α) in MyD88 −/− macrophage cell lines (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although most lipoproteins signal via TLR2, but our data showed that rLsa21 signals via both TLR2 and TLR4. This finding is consistent with various previous reports demonstrating the production of proinflammatory cytokines and chemokines through TLR2/4 by Leptospira hemolysins23, whole Leptospira or their purified components (LPS, membrane proteins) but also proteins from other bacterial pathogens like Brucella and Mycobacterium 38394041. Our results showed that rLsa21 induced cytokine production mainly through MYD88 dependent signaling pathway as there was a reduced concentration of cytokines (IL-6 and TNF-α) in MyD88 −/− macrophage cell lines (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that different PAMPs from various pathogens may activate different signaling pathways for production of proinflammatory cytokines. For instance, JNK and NF-κB signaling pathway is activated by Leptospira hemolysins23, p38 and JNK is activated by BCSP31 of Brucella 40 and MPT83 of M. tuberculosis 39, NF-κB by streptococcal hemolysins45 and p38 and NF-κB by streptolysin O and Listeriolysin4647.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 TLRs are type I transmembrane molecules which transduce their downstream signaling through the MyD88-dependent pathway or the MyD88-independent but TRIF-dependent pathway, subsequently leading to activation of mitogenactivated protein kinase (MAPK), NF-κB and IRF pathway, inducing the production of proinflammatory cytokines and IFNs (Figure 1). [5][6][7][8] Innate immune activation of phagocytes through TLRs also induces an Mst1-Mst2-Rac signaling axis to activate intracellular microbicidal killing. 9,10 RLRs, a family of cytoplasmic RNA helicases, are essential for innate recognition of viruses and are the key mechanism for the control of viral replication and dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Another promising immunodominant protein specific to Brucella is a 31 kDa protein, BCSP31. Its immune response-inducing properties are attributable to the presence of an immunogenic and protective BCSP fraction, possibly lipopolysaccharide [25] . A study indicated that the recombinant L7/L12-TOmp31 protein elicited stronger humoral and cellular immune responses and provided significant protection level against B. melitensis and B.…”
Section: Discussionmentioning
confidence: 99%